No Evidence for Self-Esteem Effects on Aggression: Findings From a Multi-Year, Multi-Informant Longitudinal Study of Mexican-Origin Families - Orth, Ulrich; Aebi, Jasmin A.; Robins, Richard W. (Psychological Science, 2026)
Researchers have long debated whether self-esteem is associated with aggression. In this preregistered research, we tested the effects of self-esteem on aggression by using statistical models that control for unmeasured time-invariant confounders. Data came from a multi-wave longitudinal study of 674 Mexican-origin families, including multi-informant assessments of children, mothers, and fathers at 1- or 2-year intervals. There was no evidence of systematic self-esteem effects on aggression, and the results held when we controlled for narcissism and when the influence of shared-method variance could be ruled out. Also, there was little evidence for effects in the reverse direction, that is, from engaging in aggression on self-esteem. One limitation was that in most cases it was not possible to test whether the self-esteem effects were curvilinear because of the nonconvergence of these models. Overall, the findings do not support either low or high self-esteem as a risk factor for aggression.